Designing a Tool for Evacuation Plan Validation: Multi-Agent Simulations with Persona-Based UI - Zanfardino, Gennaro; Di Marco, Antinisca; Tucci, Michele (IEEE/ACM International Conference on Software Engineering: Software Engineering in Society (Online), 2025)
Natural disasters (such as earthquakes) are unpredictable events that cannot be foreseen, so the unique strategy we have to reduce their impact and the risks for the citizens is to do prevention. In this context, we propose a methodology we followed to develop a highly customizable tool aimed at validating urban evacuation plans. Built with a focus on persona-based user interface (UI) design, the tool leverages software engineering methodologies to ensure scalability, dynamicity (e.g., simulating unpredictable events during the disaster), and adaptive UI for diverse user groups, including urban planners, civil protection agencies, and safety plan managers. By integrating agent-based models with Geographic Information Systems, the tool provides data-driven simulations that can be used to validate evacuation strategies. The tool was evaluated through two case studies conducted considering various urban environments, enabling iterative development through ongoing requirements elicitation and refinement in collaboration with the user groups.